Accumulation, localization, and compartmentation of transforming growth factor beta during endochondral bone development. - Jill L. Carrington; Anita B. Roberts; K C Flanders; N S Roche; A. Hari Reddi (1988)
Endochondral bone formation was induced in postnatal rats by implantation of demineralized rat bone matrix. Corresponding control tissue was generated by implanting inactive extracted bone matrix, which did not induce bone formation. At various times, implants were removed and sequentially extracted with guanidine hydrochloride, and then EDTA and guanidine hydrochloride. Transforming growth factor beta (TGF beta) in the extracts was quantitated by a radioreceptor assay. TGF beta was present in demineralized bone matrix before implantation, and the concentration had decreased by 1 d after implantation. Thereafter, TGF beta was undetectable by radioreceptor assay until day 9. From day 9-21 the TGF beta was extracted only after EDTA demineralization, indicating tight association with the mineralized matrix. During this time, the content of TGF beta per milligram soluble protein rose steadily and remained high through day 21. This increased concentration correlated with the onset of vascularization and calcification of cartilage. TGF beta was detected only between days 3-9 in the controls; i.e., non-bone-forming implants. Immunolocalization of TGF beta in bone-forming implants revealed staining of inflammatory cells at early times, followed later by staining of chondrocytes in calcifying cartilage and staining of osteoblasts. The most intense staining of TGF beta was found in calcified cartilage and mineralized bone matrix, again indicating preferential compartmentalization of TGF beta in the mineral phase. In contrast to the delayed expression of TGF beta protein, northern blot analysis showed TGF beta mRNA in implants throughout the sequence of bone formation. The time-dependent accumulation of TGF beta when cartilage is being replaced by bone in this in vivo model of bone formation suggests that TGF beta may play a role in the regulation of ossification during endochondral bone development.